Europe beyond universalism and particularism - Lindberg, Susanna; Ojakangas, Mika; Prozorov, Sergei; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Resulting from an interdisciplinary dialogue between philosophy, political science and International Relations about Europe as a political community this volume rethinks the European political project beyond the rigid opposition between universalism and particularism approaching Europe as a space of the exposure of differences to each other.
Keywords: Political science; Political theory; Democracy; European Union; Political philosophy; Human geography; Political Science and International Relations; European Union Politics; Human Geography